2006
DOI: 10.1590/s1516-35982006000800002
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de larvas de surubim-do-iguaçu (Steindachneridion melanodermatum) submetidas a diferentes dietas

Abstract: RESUMO -Para verificar o desenvolvimento de larvas de surubim-do-iguaçu (Steindachneridion melanodermatum) alimentadas com diferentes dietas, realizou-se um experimento em delineamento inteiramente casualizado, com cinco tratamentos e quatro repetições, em aquários de 35 L, cada um com 15 larvas (8,35±0,85 mm e 6,75±0,64 mg). Os tratamentos consistiram de cinco programas de alimentação: A -Artemia; R -ração; Z -zooplâncton; A+R -Artemia + ração; Z+R -zooplâncton+ração. Avaliou-se o desenvolvimento das larvas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
5
10
0
4
Order By: Relevance
“…treatments was due to the salt water carried over from the hatching period. Similar conditions were observed by Soares et al (2000) and Feiden et al (2006), who registered conductivity variation depending on whether Artemia sp. was washed or not.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…treatments was due to the salt water carried over from the hatching period. Similar conditions were observed by Soares et al (2000) and Feiden et al (2006), who registered conductivity variation depending on whether Artemia sp. was washed or not.…”
Section: Resultssupporting
confidence: 89%
“…Feiden et al (2006) also observed this pattern. Differently, other larviculture tests showed slight pH variations (Soares et al, 2000), suggesting variability as a function of plankton composition and plant conditions.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…confirm that the zooplankton is the main food for fish, especially in the first days of life, as reported to larvae of different species of fish by Fregadolli (1993), Sipaúba-Tavares (1993), Gerking (1994, Soares, Hayashi, Furuya, & Maranhão (1997), Furuya, Hayashi, Furuya, & Sakaguti (2002), Makrakis et al, 2005, Feiden et al (2006, Qu et al (2012).…”
Section: Discussionsupporting
confidence: 63%
“…Natural food is of paramount importance as it contributes with essential nutrients for growth, development and survival (Nikolsky, 1969;Mills, Widzowshi, & Jones, 1987). The shift from endogenous to exogenous feeding is a major difficulty faced in farming juveniles of rheophilic species (Gerking, 1994), as well as cannibalism that occurs in the first days of larval life (Feiden, Hayashi, & Boscolo, 2006). Therefore, studies on the diet during the early stages of fish development are of great importance to understand its role in the community, an opportunity to know one of the most critical steps for fish hatchery, which can help in the development of fish farming (Makrakis et al, 2005;Qu et al, 2012) and in determining priority areas for the maintenance of natural stocks.…”
Section: Introductionmentioning
confidence: 99%